Ultra wideband lumped Wilkinson power divider on gallium arsenide integrated passive device technology. Issue 12 (22nd September 2021) - Jiang, Yan; Hu, Kongyi; Feng, Linping; Zhang, Hai; Shi, Yongrong; Tang, Wanchun; Yu, Xinhua
Abstract: In this letter, a novel lumped Wilkinson power divider (WPD) introducing capacitors on the isolation R of ultra wideband with good isolation and insertion loss ( IL ) performance is proposed with the help of gallium arsenide (GaAs) technology. With the even and odd method, the proposed WPD is better illustrated. The fractional bandwidth (FBW) is 104% (3–9.5 GHz). Besides, the return loss is better than 13.7 dB, and the IL is better than 0.62 dB within the passband. The isolation is better than 19.5 dB from 3 to 9.5 GHz. Finally, to better illustrate the design conception, it has been fabricated on GaAs integrated passive device technology with size of 1.37 × 0.971 mm 2, that is, 0.1 × 0.072 λ g 2, measured by on‐wafer probing. All the final results of the proposed WPD are reasonably matched well.